2018
DOI: 10.29271/jcpsp.2018.09.686
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Of Serum Proangiogenic Biomarkers Between Those With And Without Diabetic Retinopathy

Abstract: Serum ET, Follistatin and EGF were significantly higher in DR patients as compared to those without DR and should be considered to be significant biomarkers of retinal complications in diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
1
1
Order By: Relevance
“…In contrast, Malik and cols. (28) did not find any differences in serum ANGPT-2 levels between patients with diabetes with or without DR. Another evidence of the involvement of ANGPT-2 in DR is related to its effect on pericyte loss in the early phases of DR development. An experimental study conducted by Hammes and cols.…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, Malik and cols. (28) did not find any differences in serum ANGPT-2 levels between patients with diabetes with or without DR. Another evidence of the involvement of ANGPT-2 in DR is related to its effect on pericyte loss in the early phases of DR development. An experimental study conducted by Hammes and cols.…”
Section: Discussioncontrasting
confidence: 59%
“…Only one study aimed to assess EGF in serum and revealed higher EGF levels in patients with diabetic kidney disease as compared with patients free of this complication [34]. Only one study revealed higher EGF serum concentration in a cohort of people with diabetic retinopathy as compared with controls without retinopathy [35]. However, T1DM patients were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these, there are also studies showing that serum FGF levels are low in DRP patients. 28,29 However, when these studies are evaluated, there is no common consensus in the literature in terms of serum FGF in DRP and DME patients. IL-1β is an endogenous pyrogen and is a cytokine that activates lymphocytes.…”
Section: Discussionmentioning
confidence: 99%